7 - Growing up Pregnant: Events of Kinship in Everyday Life - Mette Ringsted (African Sociological Review, 2004)
This paper explores how pregnant girls and young mothers, between the ages of 14 and 19, manage their social relations during pregnancy and early motherhood. Whereas most of the pregnant girls and young mothers in this study lived as 'unwanted family members ' others were reintegrated into their families. The paper focuses on how they actively negotiate and form 'relatedness ' to reduce uncertainty in their daily life, and particularly how they and their children struggle not to be excluded from reciprocal family responsibilities. During recent decades, people in Tanzania as in most qf sub-Saharan Africa have been experiencing major changes in the family structure. Modernisation and urbanisation, and more recently the HIVIAJDS pandemic, have also resulted in the disintegration of social support networb and high Level of mobility also among young adolescents and children. The research is based on fieldwork in Muheza, a roadside town in north-eastern Tanzania (2002-2003).